I'll get you started on #1
sin(theta) - sin(theta)/cos(theta) =0
sin(theta)cos(theta) / cost(theta)
- sin(theta)/cos(theta) =0
(sin(theta)cos(theta) - sin(theta)) / cos(theta)=0
Therefore sin(theta)cos(theta) - sin(theta)=0
sin(theta) (cos(theta) - 1) =0
Now solve sin(theta)=0 and cos(theta)=1
2007-01-08 15:07:45
·
answer #1
·
answered by Professor Maddie 4
·
1⤊
0⤋
1a. sinθ - tanθ = 0
sinθ - (sinθ/cosθ) = 0
(sinθ/cosθ)(cosθ - 1) = 0
sinθ = 0 => θ = k*180 for k being an integer
OR
cosθ - 1 = 0 => cosθ = 1 => θ = k*360 for k being an integer
So to keep the answer between 0 and 360 degrees, we only need to consider solutions for when k = 0, 1, 2 (possibly). Note that plugging in k > 2 would result in an answer beyond 360 for sure.
θ = 0, 180, 360 are the only answers that lie in your interval.
1b. 2sin2θ = √2
You need to get θ by itself.
sin2θ = (√2)/2
2θ = 45 + k*360 for k being an integer
OR
2θ = 135 + k*360 for k being an integer
So our answer becomes
θ = 45/2 + k*180 for k being an integer
OR
θ = 135/2 + k*180 for k being an integer
To keep the angle between 0 and 360 degrees, we just need to consider k = 0, 1
θ = 45/2, 135/2, 405/2, 495/2 are the angles the lie in your interval.
1c. sinθ = 1 + cosθ
Square both sides.
(sinθ)^2 = (1 + cosθ)^2
Expand the right side.
(sinθ)^2 = 1 + 2cosθ + (cosθ)^2
Recall the famous identity: (sinθ)^2 + (cosθ)^2 = 1
(sinθ)^2 = (sinθ)^2 + (cosθ)^2 + 2cosθ + (cosθ)^2
Subtract (sinθ)^2 from both sides.
0 = 2(cosθ)^2 + 2cosθ
Divide 2 from both sides.
0 = (cosθ)^2 + cosθ
Factor out cosθ from the right side.
0 = cosθ(cosθ + 1)
cosθ = 0 => θ = 90 + k*180 where k is an integer
OR
cosθ = -1 => θ = 180 + k*360 where k is an integer
To keep θ in the proper interval, we only really need to consider k = 0, 1
θ = 90, 180 are the only angles that lie in your interval.
2007-01-08 15:20:58
·
answer #2
·
answered by alsh 3
·
1⤊
0⤋
1)
a) sin(t) - tan(t) = 0
Change the left hand side to sines and cosines.
sin(t) - sin(t)/cos(t) = 0
Put under a common denominator.
[sin(t)cos(t) - sin(t)]/[cos(t)] = 0
Factor sin(t) out of the numerator.
sin(t) [cos(t) - 1] / cos(t) = 0
Factor the fraction of 1/cos(t).
[sin(t)/cos(t)] [cos(t) - 1] = 0
[tan(t)] [cos(t) - 1] = 0
Now, equate each of those to 0 and solve.
tan(t) = 0, cos(t) - 1 = 0.
tan(t) = 0 implies t = {0, pi}
cos(t) - 1 = 0 implies cos(t) = 1, which means t = 0.
Therefore, our solutions are t = {0, pi, 2pi}, or, in degrees,
t = {0, 180, 360}
2. 2sin2(t) = sqrt(2)
Divide both sides by 2,
sin(2t) = sqrt(2)/2
Sine is equal to sqrt(2)/2 at two places: pi/4, 3pi/4. However, we must double our solutions because we have 2t. Our solutions will be:
2t = {pi/4, 3pi/4, pi/4 + 2pi, 3pi/4 + 2pi}
2t = {pi/4, 3pi/4, 9pi/4, 11pi/4}
Now, divide each solution by 2, which is the same as multiplying them by 1/2.
t = {pi/8, 3pi/8, 9pi/8, 11pi/8}
Converted to degrees,
t = {22.5, 67.5, 202.5, 247.5}
3. sin(t) = 1 + cos(t)
To solve this, let's move the cos(t) to the left hand side.
sin(t) - cos(t) = 1
Square both sides, to obtain
sin^2(t) - 2sin(t)cos(t) + cos^2(t) = 1
sin^2(t) + cos^2(t) - 2sin(t)cos(t) = 1
Note the identity sine squared x plus cos squared x = 1.
1 - 2sin(t)cos(t) = 1
-2sin(t)cos(t) = 0
2sin(t)cos(t) = 0
Note that 2sin(t)cos(t) = sin(2t) by the double angle identity, so
sin(2t) = 0, and it follows that (note: we have to double our solutions because we have 2t)
2t = {0, pi, 2pi, 3pi}. Dividing both sides (and therefore each term) by 2, we get
t = {0, pi/2, pi, 3pi/2}
Because squaring an equation may add unnecessary solutions, we have to TEST each value.
sin(t) = 1 + cos(t).
Test t = 0: sin(0) = 0, 1 + cos(0) = 1 + 1 = 2.
Reject t = 0.
Test t = pi/2: sin(pi/2) = 1, 1 + cos(pi/2) = 1 + 0 = 1.
This one checks out.
Test t = pi: sin(pi) = 0, 1 + cos(pi) = 1 + (-1) = 0.
This one checks out.
Test t = 3pi/2; sin(3pi/2) = -1, 1 + cos(3pi/2) = 1 + 0 = 1.
Reject t = 3pi/2.
Therefore
t = {pi/2, pi}, or, converted to degrees
t = {90, 180}
2007-01-08 15:12:19
·
answer #3
·
answered by Puggy 7
·
2⤊
0⤋
cos x/sec x + sin x/csc x = a million secx= a million/cosx cscx=a million/sinx so that you get cosx/(a million/cosx) + sin x/(a million/sin x) = a million cos^2x + sin^2x = a million cos x/ (sec x sin x) = csc x - sin x cosx/ (sinx/cosx) = a million/sinx - sinx cos^2x/sinx = a million/sinx - sinx multiply by sinx to get cos^2x = a million - sin^2x sin^2x + cos ^2x = a million
2016-12-02 00:56:37
·
answer #4
·
answered by ? 4
·
0⤊
0⤋